2008
DOI: 10.1007/s11661-008-9591-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Machinability of the Al-SiC Metal Matrix Composite Using the Dynamic Material Model

Abstract: The dynamic material model (DMM) method has been widely used for the macroscopic description of flow, fracture, and workability of materials under hot deformation. This investigation is aimed at proposing a new methodology for the optimization of hot machinability of a material using the DMM stability criteria. The constitutive flow behavior of Al-20 pct SiC has been evaluated in the temperature range 50°C to 350°C and the cutting velocity in the range from 25 and 300 m/min with the view to optimizing its mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The occurrence of multiple slopes in the variations of skewness and kurtosis with time can possibly be attributed to the occurrence of different wear mechanisms in the composite. Scanning electron microscopy (SEM) results were reported in an earlier paper (Mohan et al, 2008). This showed that the cutting tool experiences abrasive wear at the flank face, as well as chip breakage and scooping of the SiC particles.…”
Section: Statistical Analysis Of Ae Signalsmentioning
confidence: 82%
“…The occurrence of multiple slopes in the variations of skewness and kurtosis with time can possibly be attributed to the occurrence of different wear mechanisms in the composite. Scanning electron microscopy (SEM) results were reported in an earlier paper (Mohan et al, 2008). This showed that the cutting tool experiences abrasive wear at the flank face, as well as chip breakage and scooping of the SiC particles.…”
Section: Statistical Analysis Of Ae Signalsmentioning
confidence: 82%
“…Table 1 lists various recommended turning parameters for industry consideration based on optimization studies from Refs. [119][120][121][122][123][124].…”
Section: Surface Integrity and Machining Efficiencymentioning
confidence: 99%
“…Under force, the stress of the matrix is unequal to that of SiC particles. According to Mohan et al [29] in the cutting process of composites, when the matrix deforms plastically, the SiC particles may only deform elastically to break, and also the boundary of the matrix and the SiC particles may break between the tool and reinforcing particles, which causes severe abrasive wear on the tool flank. This is because when the bond is broken, the SiC particles will gain higher kinetic energy due to turning of workpiece during machining.…”
Section: Effect Of Sic Particlesmentioning
confidence: 99%